2022
DOI: 10.1002/term.3345
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resolvin D1 on bone regeneration in a rat calvarial defect model

Abstract: Resolvin D1 (RvD1) is a pro‐resolving lipid mediator of inflammation, endogenously synthesized from omega‐3 docosahexaenoic acid. The purpose of this study was to investigate the effect of RvD1 on bone regeneration using a rat calvarial defect model. Collagen 3D nanopore scaffold (COL) and Pluronic F127 hydrogel (F127) incorporated with RvD1 (RvD1‐COL‐F127 group) or COL and F127 (COL‐F127 group) were implanted in symmetrical calvarial defects. After implantation, RvD1 was administrated subcutaneously every 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Xiaofeng et al demonstrated improved bone healing in rat-calvaria model. Rats were treated with collagen scaffolds, in addition to weekly subcutaneous (SC) injections of RvD1 (39). Subcutaneous tissue enables slow release of molecules due to its special tissue architecture and its combination with collagen scaffolds, thereby reducing the need for frequent injections and their related side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Xiaofeng et al demonstrated improved bone healing in rat-calvaria model. Rats were treated with collagen scaffolds, in addition to weekly subcutaneous (SC) injections of RvD1 (39). Subcutaneous tissue enables slow release of molecules due to its special tissue architecture and its combination with collagen scaffolds, thereby reducing the need for frequent injections and their related side effects.…”
Section: Discussionmentioning
confidence: 99%
“…126 It has been demonstrated that collagen/Pluronic F127 hydrogel loaded with resolvin D1 (RvD1), derived from omega-3 docosahexaenoic acid, effectively reduced inflammation and promoted calvarial defect repair in rats. 127 Hydrogels have also been employed as delivery carriers for sustained release of anti-inflammatory drugs in bone tissue regeneration. For instance, Chauhan et al loaded dexamethasone (Dex) into an oxidized pullulan (OP)/PEG hydrazine hydrogel, providing pH-sensitive sustained release and improved chronic inflammatory conditions.…”
Section: Local Delivery Hydrogels To Restore Immune Homeostasismentioning
confidence: 99%
“…In rat calvarial defects, a recent work by Jiang et al 3 showed that RvD1 had enhanced bone regeneration and vascularization potential. Similarly, Pinto et al 9 have shown that RvD1 may be a viable therapeutic bioagent for osseous regeneration following the placement of allografts.…”
Section: Introductionmentioning
confidence: 99%
“…4 Previous studies have reported better bone regeneration with adjunctive use of platelet-rich plasma (PRP), mesenchymal stem cells (MSCs), bone morphogenic proteins (BMP), specialized pro-resolving mediators (SPMs) and platelet-derived growth factor (PDGF). 3,[5][6][7][8][9] An essential element of inflammatory responses is the resolution of inflammation. 10 Previously, it was understood that after the initiating stimulus had been eliminated, there would be a passive, progressive reduction in inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation